OS IMPACTOS PROVOCADOS NA CADEIA PRODUTIVA DA CARNE SUÍNA A PARTIR DAS RESTRIÇÕES ÀS EXPORTAÇÕES - Sparemberger, Cristian; Dorneles, Vinicius R.; Zamberlan, Luciano; Büttenbender, Pedro L.; Sparemberger, Ariosto (Salão do Conhecimento, 2013)
Resumo